2018
DOI: 10.2298/jsc171110018z
|View full text |Cite
|
Sign up to set email alerts
|

Use of honeybees (Apis mellifera L.) as bioindicators of spatial variations and origin determination of metal pollution in Serbia

Abstract: Honeybees have been proposed and used as bioindicators for the last few decades, because of their nature. Until now they have mostly been used to determine the present pollution and to distinguish the differences between the sampling locations and the sampling periods. With the use of multivariate statistical methods honeybees can also be used to distinguish the origin of this pollution. In this study the concentrations of Al,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The values related to the bees sampled in the three locations in Milano in the present study are lower than those found for Pb (mean 0.602 mg g À1 ; 0.248-1.396 lg g À1 ) in a previous study conducted in Milano (Costa et al 2019) during the Expo 2015 time, maybe for the lower atmospheric concentration of pollutants related to the lower road traffic, in comparison with that occurred during the months of Expo. This decline in Pb biaccumulated on bees can be explained by recent findings of Zari c et al (2018aZari c et al ( , 2018b, who observed the decline of Pb concentrations during the years, for the "mitigation" of Pb anthropogenic sources in urban sites.…”
Section: Discussionmentioning
confidence: 65%
“…The values related to the bees sampled in the three locations in Milano in the present study are lower than those found for Pb (mean 0.602 mg g À1 ; 0.248-1.396 lg g À1 ) in a previous study conducted in Milano (Costa et al 2019) during the Expo 2015 time, maybe for the lower atmospheric concentration of pollutants related to the lower road traffic, in comparison with that occurred during the months of Expo. This decline in Pb biaccumulated on bees can be explained by recent findings of Zari c et al (2018aZari c et al ( , 2018b, who observed the decline of Pb concentrations during the years, for the "mitigation" of Pb anthropogenic sources in urban sites.…”
Section: Discussionmentioning
confidence: 65%
“…Conti and Botré (2001) • High traffic levels contributed to greater levels of Cd, Co, Mn, Cu, Ba, Fe, Ni, and Sr in honeybees. Zarić et al (2016Zarić et al ( , 2018 • Concentrations of Pb in honeybees, wax and honey were extremely similar to current or historical levels in the environment. Zhou et al (2018) Paper wasps Polistes dominulus • Traffic density was directly correlated with Pb concentrations in larval faecal masses.…”
Section: Hazardmentioning
confidence: 58%
“…Considering that the results showed higher concentrations of U, Se and V in the area impacted by thermal power plants Kostolac A and Kostolac B, it can be assumed that the elements originate from coal combustion occurring in these power plants. It was already pointed out that these power plants are sources of high concentrations of Al, Cr and Fe found in the region ( Zarić et al, 2016 ; Zarić et al, 2018 ). Earlier studies showed that U comes from the combustion of coal in thermal power plants ( Sengupta & Agrahari, 2017 ).The same was observed for coal fired power plants in Serbia ( Životić et al, 2008 ; Ćujić et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%